Linearization method for MINLP energy optimization problems - Anastasiia Zhadan; Alexey Martemyanov; Alexander Allahverdyan; Ovanes Petrosian; Hongwei Gao (Scientific Reports)
Abstract Optimal scheduling of battery energy storage system plays crucial part in distributed energy system to provide stability and reduce user costs. Non-linear equipment characteristics (e.g., battery energy storage systems (BESS), electric power conversion have non-linear efficiency curves) can lead to errors in stored energy between the schedule and actual operation. This research proposes a technique to mitigate the occurrence of such errors in the BESS charging/discharging planning process by linearizing equipment nonlinear characteristics. This paper presents the implementation and comparison of three linearization techniques: special ordered set type 1 (SOS1), special ordered set type 2 (SOS2), and the Taylor method for the modeling and control of charging-discharging BESS, a DC/AC and AC/DC converters where non-linear efficiency curves are used. Also, the paper offers heuristics that allow effective selection of initial points for each of the intervals on the efficiency curves. There are presented experimental results confirming the effectiveness of the proposed control with different linearization approaches for solving operational problems caused by nonlinear characteristics of the equipment.